ANTIBACTERIAL EFFECT OF MAULI BANANA STEM EXTRACT, BASIL LEAF EXTRACT, AND THEIR COMBINATION ON Staphylococcus aureus - Almadina Latanza; Maharani Laillyza Apriasari; Yusrinie Wasiaturrahmah (FKG Unlam, 2020)
ABSTRACTIntroduction: Mauli banana stem and basil leaf extracts have an antibacterial effect on Staphylococcus aureus because they contain flavonoid, saponin, alkaloid, tannin, and eugenol. 1% povidone iodine is commonly used as an antiseptic and gargle for recurrent aphthous stomatitis caused by Staphylococcus aureus. Prolonged use of 1% povidone iodine is notable to possess adverse effects. Objective: To prove the antibacterial effect of mauli banana stem extract with 25% concentration, basil leaf extract with 12.5% concentration, and mauli banana stem and basil leaf combination extract with 25%, 50%, and 75% concentration on Staphylococcus aureus and compared to 1% povidone iodine. Methods: This study was applying the true experimental design with post-test only and control group design which consisted of 6 treatments. Group I was given with Mauli banana stem extract with 25% concentration, group II with basil leaf extract with 12.5% concentration, group III, IV, and IV with mauli banana stem and basil leaf combination extract with 25%, 50%, and 70% concentration, respectively. Meanwhile, group VI was given with 1% povidone iodine as a positive control. Each treatment had 4 times repetition. Antibacterial effectivity was assessed from the inhibition zone measurement of Staphylococcus aureus growth using the diffusion method. Results: This study revealed that the mean inhibition zone formed in group I was 6-6.2 mm, group II was 6-6.2 mm, group III was 6-6.9 mm, group IV was 7.6-8 mm, group V was 8-8.5 mm, and group VI was 10.6-11.8 mm. Conclusion: The antibacterial efficacy of mauli banana stem extract at 25% concentration, basil leaf extract at 12.5% concentration, mauli banana and basil leaf combination extract at 25%, 50%, and 75% concentration on Staphylococcus aureus has been proven but not equal to 1% povidone iodine’s efficacy. Keywords: Basil leaf extract, Diffusion method, Inhibition zone, Mauli banana stem extract, Staphylococcus aureus,.